Effectiveness of a short message service intervention to motivate people with positive results in preliminary colorectal cancer screening to undergo colonoscopy: A randomized controlled trial. Issue 13 (2nd March 2019) - Wu, Yanan; Liang, Yingru; Zhou, Qin; Liu, Huazhang; Lin, Guozhen; Cai, Wenfeng; Li, Yan; Gu, Jing
Abstract : Background: Colonoscopy adherence among populations at high risk for colorectal cancer (CRC) is crucial for the early diagnosis and treatment of CRC, but the adherence rate has been found to be poor. A short message service (SMS) is effective in promoting cancer screening, but its effectiveness in promoting colonoscopy among populations at high risk for CRC has not been well studied. Methods: In this randomized controlled trial conducted in Guangzhou, China, participants who had tested positive during preliminary CRC screening (a high‐risk factor questionnaire and/or an immunochemical fecal occult blood test) but had not undergone colonoscopy were randomized into low‐frequency (monthly) intervention, high‐frequency (biweekly) intervention, and control groups. The 2 intervention groups received behavioral theory–based SMS for 6 months. Data were obtained from the CRC screening database. The outcome was undergoing a colonoscopy examination. Results: For the 1362 participants, the rates of colonoscopy adherence were 5.2%, 6.0%, and 10.5% at month 3 and 7.1%, 9.6%, and 13.7% at month 6 in the control, low‐frequency intervention, and high‐frequency intervention groups, respectively. After adjustments for potential confounders, the high‐frequency intervention group was approximately twice as likely as the control group to undergo colonoscopy (adjusted hazard ratio, 1.99; 95% confidence interval, 1.32‐3.01), whereas the difference between the low‐frequency intervention and control groups was not statistically significant. The cost of SMS to increase colonoscopy uptake by 1 in the high‐frequency intervention group was US $2.7. Conclusions: Text messages sent biweekly for 6 months to patients with positive preliminary screening results could increase colonoscopy adherence. SMS could be a prioritized intervention for promoting colonoscopy in large community‐based populations. Abstract : Twelve text messages sent biweekly could double colonoscopy adherence in the population at high risk for colorectal cancer. A short message service intervention could be prioritized in colonoscopy promotion in community‐based populations.